Teachers' Perception of Four-Tier Diagnostic Test Instrument Equipped with Self-Diagnosis Sheet to Identify Students' Misconception on Linear Motion Material - Intan Khasana; Viyanti; Undang Rosidin (Jurnal Penelitian Pendidikan IPA, 2024)
The purpose of this study was to determine the perception of physics teachers towards the four-tier diagnostic test instrument equipped with self-diagnosis sheet to identify students' misconceptions on linear motion material. The research method used in this study is a mixed method with Sequential Explanatory Design.  Data were collected first using a questionnaire and then analyzed using descriptive analysis. The questionnaire was distributed to 14 physics teachers and 96 high school students in Lampung Province. The results showed that teachers have a positive perception of the use of a four-tier diagnostic test instrument equipped with a self-diagnosis sheet feature to identify students' misconceptions on straight motion material.  The results showed that 87% of teachers had never identified students' misconceptions on straight motion material. The results also show that 90% of teachers only use the results of daily tests as a benchmark to determine the misconceptions experienced by students. Misconceptions in this straight motion material certainly affect the learning outcomes of students, it is known that only 46% of students reach the KKM on straight motion material. And the results of the questionnaire show that 95% of teachers have never identified the misconceptions of students on linear motion material to make and use any type of multilevel diagnostic test instrument because the teacher has no difficulty in making it. So an effort is needed to overcome these problems, namely by making valid, practical, and effective multilevel diagnostic test instruments.  Based on the results of the study, it can be concluded that a four-tier diagnostic test instrument equipped with a self-diagnosis sheet is needed to identify students' misconceptions on linear motion material.